Raw-Material Provenience of the Solutrean Diagnostics from Gruta do Caldeirão (Tomar, Portugal) - Matias, Henrique (2019)
The flints used to produce the diagnostic Solutrean stone tools from Gruta do Caldeirão are classified, their geological and geographical origin is determined, and results are compared with available data for three other regions of Iberia: the Côa Valley and the Sicó Massif, in Portugal, and Cantabria, in northern Spain. Three of the five Caldeirão flint types have sources less than 30 km away. Such catchment sizes are like those inferred for most silicifications found at Buraca Grande (Sicó Massif). Longdistance circulations — such as the ones recognized in some Côa Valley and Cantabrian sites — have not been identified. However, the other two Caldeirão flint types remain of unknown origin, so broader procurement ranges cannot be excluded.